Sustainable and resilient global practices : advances in responsiveness and adaptation - Andersen, Torben Juul (Emerald studies in global strategic responsiveness., 2024)
We need to develop a better understanding of how to generate effective strategic adaptation in times of abrupt environmental changes. The global interdependencies across specialized economic functions and markets require that business activities co-evolve across interacting public-private relationships where organizations can engage around viable ecosystems forming a sustainable path for the future. The ability to develop sustainable solutions thrives on innovative behaviors across networks of collaborative relationships and we need to enhance our understanding about how they can be established and managed. The chapters presented here by global scholars fill the void in current knowledge with the aim of generating important leads for forthcoming scholarship efforts for the benefit of business and society. Emerald Studies in Global Strategic Responsiveness aspires to disseminate new inspiring research insights as a potential catalyst for the development of effective approaches to deal with the exposures imposed by dynamic complexities in the global business environment. The implied organizational and societal challenges require effective responses from both public and private organizations induced by supportive policy initiatives.